Biodegradable magnesium alloy coated by fluoridated hydroxyapatite using MAO/EPD technique. (August 2014) - Razavi, M.; Fathi, M.; Savabi, O.; Vashaee, D.; Tayebi, L.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, a nanostructured fluoridated hydroxyapatite (FHA) coating was used on AZ91 magnesium to improve its corrosion resistance and in vitro bioactivity. The coating was made through micro arc oxidation (MAO) and electrophoretic deposition (EPD) method. After characterising phase composition and surface morphology, the corrosion and the in vitro bioactivity behaviours of the coated materials were investigated by electrochemical measurements and immersion tests in simulated body fluid (SBF). The results confirmed the enhancement of the corrosion resistance and the bioactivity of the AZ91 alloy coated with nanostructured FHA. Therefore, the surface treatment introduced in this paper may be an apt approach to make magnesium alloys more suitable for orthopedic applications.